2008
DOI: 10.2527/jas.2006-650
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of zinc from zinc sulfate and zinc proteinate by ovine ruminal and omasal epithelia1,2

Abstract: Uptake and transport of Zn from (65)Zn-labeled ZnSO(4) and Zn proteinate (ZnProt) by ruminal and omasal epithelia were examined by using a parabiotic chamber system. Uptake was measured during a 4-h incubation with 10, 20, or 200 microM Zn as ZnSO(4) or ZnProt in the mucosal buffer (pH 6.0, Krebs-Ringer phosphate). Zinc uptake and transport were also evaluated after simulated ruminal digestion. Buffered ruminal fluid contained a feed substrate and 10 or 200 microM added Zn as ZnSO(4) or ZnProt. In a preliminar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Similar results were reported also by other authors (Puchala et al 1999;Zitnan et al 2003;Arelovich et al 2008;Wright et al 2008).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar results were reported also by other authors (Puchala et al 1999;Zitnan et al 2003;Arelovich et al 2008;Wright et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…various inorganically and organically bound forms; in veterinary and human medicine it is also used for its antibacterial effect (Puchala et al 1999;Wright et al 2008;Pechová et al 2006Pechová et al , 2009Screenivasan et al 2009). There is absence of literature describing the effects of oral supplementation of different forms of zinc on ruminal mucosa of kids.…”
mentioning
confidence: 99%
“…Moreover, Also, Wright et al [86] they proved that trace elements as zinc showed restoration towards normal level after natural oils supplementation due to improved disease state since the cause affecting their changes were diminished. Supplementation of Zn, during times of oxidative stress may reduce oxidative damage to white blood cells and increase disease resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The mineral content can be determined chemically whereas bioavailability is much more difficult to be estimated (Singh, 2013). The majority of minerals are absorbed only minimally across the rumen epithelium and they cannot be absorbed by the animal until they reach the small intestine (Wright et al, 2008). Dissolved minerals in the reticulorumen, omasum, and abomasum can form indigestible compounds with polyphenols, phytates, oxalates and some sugars that pass into the manure as indigestible waste (Spears, 2003).…”
Section: Introductionmentioning
confidence: 99%